Role of Residues 121 to 124 of Vesicular Stomatitis Virus Matrix Protein in Virus Assembly and Virus-Host Interaction - Connor, John H. (American Society for Microbiology, 2006)
The recent solution of the crystal structure of a fragment of the vesicular stomatitis virus matrix (M) protein suggested that amino acids 121 to 124, located on a solvent-exposed loop of the protein, are important for M protein self-association and association with membranes. These residues were mutated from the hydrophobic AVLA sequence to the polar sequence DKQQ. Expression and purification of this mutant from bacteria showed that it was structurally stable and that the mutant M protein had self-association kinetics similar to those of the wild-type M protein. Analysis of the membrane association of M protein in the context of infection with isogenic recombinant viruses showed that both wild-type and mutant M proteins associated with membranes to the same extent. Virus expressing the mutant M protein did show an approximately threefold-lower binding affinity of M protein for nucleocapsid-M complexes. In contrast to the relatively minor effects of the M protein mutation on virus assembly, the mutant virus exhibited growth restriction in MDBK but not BHK cells, a slower induction of apoptosis, and lower viral-protein synthesis. Despite translating less viral protein, the mutant virus produced more viral mRNA, showing that the mutant virus could not effectively promote viral translation. These results demonstrate that the 121-to-124 region of the VSV M protein plays a minor role in virus assembly but is involved in virus-host interactions and VSV replication by augmenting viral-mRNA translation.